A study on the perception of the provision of bicycle commuting facilities to increase bicycle commuting in central business districts in Metro Manila - Josef, Jose Feliciano C. (School of Urban and Regional Planning, University of the Philippines Diliman, 2016)
This study explores how bicycle commuting can be improved through the provision of bicycle commuting facilities, as a mode of transportation for work trips in Metro Manila, where traffic conditions have gone from bad to worse, and are expected to worsen until 2030. The benefits of bicycle commuting can address transport-related problems brought about by the dependency on motorized transport as the primary mode of transportation. One of the direct benefits of bicycle commuting to daily work trips is that it allows for faster travel times for distances considered as bike able, which is from 0-10 kilometers. By doing so, bicycle commuters avoid the inconvenience of being stuck in traffic and spending too much time commuting. However, deterrents to bicycle commuting are plentiful, particularly on concerns about safety during transit. This is because of the lack of bicycle lanes in Metro Manila which leaves bicycle commuters no other option but to cycle on streets alongside motorists, who have little to no respect for them. But despite this problem on bicycle lanes, it can be observed that there as people that continue to commute using bicycles. This can be seen as an opportunity to provide other types of bicycle commuting facilities that address other deterrents such as the inconvenience brought about by the humid weather, and concerns on security that can be attributed to the lack of bicycle parking at work locations or at destination points.Findings from the study, show that bicycle commuting facilities-bicycle lanes, bicycle parking, shower rooms and lockers- are generally perceived to be factors that can increase or convince people to bicycle commute. But among the four facilities, bicycle parking was identified as the facility that would increase the number of bicycle commuters or convince people to shift to bicycle commuting the most by working respondents based on bicycle user type and bicycle commuting experience. But as each facility address different concerns at different stages of bicycle commuting, the potential increase in bicycle commuting can be better realized if the facilities are implemented collectively.